The Influence of Threats and Budget Capability on the Development of Domestic Alpahankam Technology - Panjaitan, Marsono; Anwar, Baharudin; Darma, Ardian Budi (AGUSPATI Research Institute, 2025)
The development of domestic defense and security equipment technology (Alpalhankam) is a strategic factor in strengthening national sovereignty. External threats of military, economic, and technological nature, along with the government’s budget capacity, are two main factors influencing the success of defense technology development. This study aims to analyze the influence of external threats and budget capacity on the development of Alpalhankam technology in Indonesia. The research method used is quantitative, with a population consisting of staff and experts in the defense industry, and a sample of 50 respondents selected through purposive sampling. Data were collected using questionnaires, interviews, and documentation, and analyzed through validity and reliability tests, descriptive statistics, and linear regression. The results show that external threats have a positive and significant influence on technology development (B = 0.431, p = 0.000), while budget capacity also has a positive and significant influence with a higher coefficient (B = 0.512, p = 0.000). The correlation among variables indicates a strong relationship, with an R² of 0.622, suggesting that 62.2% of the variation in technology development can be explained by the two independent variables. These findings highlight the importance of synergy between threat mitigation and budget optimization to enhance the capacity and independence of the national defense industry.